Impacts De L’urbanisation Sur Les Caractéristiques Morphologiques Et Les Apports En Eau Du Barrage Hydro-Agricole De Nanan Dans Le Département De Yamoussoukro (Côte d’Ivoire) - Kouyate, Sawadogo Zounabo Épouse; Brou, Yao Casimir; Soro, Gneneyougo Emile; Goula, Bi Tié Albert (European Scientific Journal, ESJ, 2018)
The significant decrease in the water level of the Nanan agricultural dam is becoming very worrying for rice farmers. In this study, we analyzed the land use dynamics of dam watershed and its impacts on morphological characteristics and reservoir inflow. This analysis was conducted by coupling the satellites images of Landsat sensors over a thirty years, Digital Terrain Model (DTM) and direct field observation. The classification of Thematic Mapper (1986), Enhanced Thematic Mapper+ (2000) and Operational Land Imager (2015) images has gave respectively an overalls accuracies of 99.01%, 96.62% and 94.6% and kappa index of 0.98, 0.95 and 0.91. The analysis of the land use dynamics of the catchment showed that its urbanization started before 1986 and accelerated after 2000 with the transfer of the political capital of Abidjan to Yamoussoukro. The area of dam watershed was reduced between 1986 (8,272 km²) and 2000 (7,348 km²).After 2000, the construction of road infrastructures on the watershed led to a subdivision of the watershed into two sub-watersheds separated by a culvert. The current configuration is an upstream basin with an area of 4.30 km² and the downstream basin an area of 3.048 km². As a hydrological consequence of urbanization in watershed is runoff water has increased from 41.7 mm in 1986 to 43.30 mm in 2000 and 46.40 mm in 2015. However, inter-basin water transfer and grass cover at the entrance to the basin slowed runoff and reduced by a third the flow to the reservoir dam. This situation led to a decrease in the water level in the reservoir of the Nanan hydro-agricultural dam.